ANALISIS TEMA DAN AMANAT DALAM NOVEL “MARIPOSA” KARYA LULUK HIDAYATUL FAJRIYAH - Wuni Nurfauziah; Ika Mustika; Agus Priyanto (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Literary work is an essay that evokes feelings, thoughts, and experiences that are poured into writing. Novel is one of the literary works created by the author's imagination which is written in a narrative and contains stories about the problems of one's life. Every novel has intrinsic elements, such as theme and message. These elements can attract the interest of readers who come from various circles. The analysis of the novel in this study aims to describe the themes and messages contained in the novel "Mariposa" by Luluk Hidayatul Fajriyah. This research method is descriptive qualitative method. The data used, namely the theme and mandate in the novel "Mariposa". The data source used is the novel "Mariposa" by Luluk Hidayatul Fajriyah. The steps taken in analyzing the data are reading the novel "Mariposa", collecting data, analyzing the data that has been collected, selecting and sorting the data that has been analyzed, and describing the themes and messages in the novel. Based on the research results, the novel "Mariposa" by Luluk Hidayatul Fajriyah has two types of themes and two types of messages. The two types of themes are major themes about the struggle of love and minor themes about friendship. The mandate contained in the novel "Mariposa", namely the explicit mandate and the implicit mandate.